A hydroxyl-functionalized microporous organic polymer for capture and catalytic conversion of CO2. Issue 80 (15th August 2016) - Zhang, Xiao; Lv, Yan-Zong; Liu, Xiao-Liang; Du, Guo-Jing; Yan, Shi-Hao; Liu, Jian; Zhao, Zhen
Abstract : A novel hydroxyl-functionalized microporous organic polymer (HF-MOP ) exhibited good CO2 capture performance and excellent catalytic activity in cycloaddition reaction. Abstract : A novel hydroxyl-functionalized microporous organic polymer (HF-MOP ) was designed and synthesized through simple polycondensation reaction of 2, 3-dihydroxyterephthalaldehyde and 2, 6, 14-triaminotriptycene. The polymer exhibited good CO2 capture performance (8.7 wt%, 273 K and 1 bar), and simultaneously functioned as a metal-free heterogeneous catalyst for the cycloaddition of CO2 with a series of epoxides to cyclic carbonates (82–91%) under mild and solvent-free conditions. Moreover, HF-MOP can be recycled five times without a significant decrease in catalytic activity.